Genealogies, Genomes, and Histories in the Pacific - Matsuda, Matt K. author. aut Link
IX, 293 p. 1 illus.
Keywords: This work explores a panorama of historical studies, focused on the historical tensions between genealogical knowledge and well-known Pacific Islander engagements with genomic research in a postwar era of simultaneous decolonization and Big Science. These include connected examinations of ancient voyaging reconstruction and migration routes, “warrior genes,” a noted life-form patent case, questions of genetic engineering and biopiracy, the repatriation of ancestral remains, legacies of nuclear testing, and conflicts with the Human Genome Diversity Project in Oceania. It also considers the persistence of eugenics and race thinking within blood quanta and dispossession histories and how other histories are being written. This single-volume overview situates these multiple engagements within a narrative framework of postwar racism and anti-racism, the technological promises of genetic science, and the cultural and political struggles and assertions of Indigenous islanders, whose voices structure and shape the arguments. Matt Matsuda is Professor of History at Rutgers University, USA. He teaches Modern European and Asia/ Pacific global-comparative histories in the Rutgers-New Brunswick History Department, where he has been since 1993.